Finger Prick to Finger Tip: Use of Mobile Phone Technology to Send PKU Blood Results. (24th June 2018) - Clark, Anne; Deverell, Deirdre; Corcoran, Emma; Macauley, Margaret; Newcombe, Nicola; Branagan, Peter; Coughlan, Aoife; Daly, Eimear; Moore Heslin, Aoibhin; Crushell, Ellen; Hughes, Joanne; Knerr, Ina; et al.
Abstract : The Metabolic Dietetic Team in the National Centre for Inherited Metabolic Disorders (NCIMD) in Ireland deals with approximately 120 weekly phenylalanine (Phe) levels for both adults and children. A review of 500 Phe levels highlighted that 52% of the results were within the target range. Collaboration between information and communication technologies (ICT) departments, metabolic laboratory, and metabolic dietitians enabled the development of the PKU texting system. Following a successful pilot study, the system was then offered to all PKU patients aged over 2 years. The Phe is analysed and authorised on the laboratory system. The demographics are matched with the patient mobile phone number. Text messages are then validated and sent by the dietitian via a web portal using the Defero SMS texting service. Approximately 290 patients/families currently use the texting system. In order to assess the effectiveness of this quality improvement initiative, a patient survey was carried out in 2017. This showed 87% rated the system as either very good or excellent. 94% agreed it was time saving. 84% felt there was no influence on dietary compliance. Analysis of financial implications on dietetic time over 21 months revealed savings of €3, 275 and 580 hours of dietetic time. There is no evidence, two years after implementation, that the system has had an effect on either the Phe levels in terms of recommended range or frequency of sampling.